Analisis Keunggulan Bersaing Berkelanjutan Ekowisata Mangrove Lantebung Kota Makassar - Sri Wulandari; Haerun Nikma; Hartati Tamti (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Institut Teknologi dan Bisnis Maritim Balik Diwa, 2024)
Preserving the mangrove ecosystem is very important for carrying out sustainable ecosystem management because the level of competition for eco-tourism in the mangrove ecosystem is increasing. An ecotourism can win the competition if it has a competitive advantage compared to its competitors. This idea of ​​competitive advantage comes from a resource-based perspective. We must have certain criteria so that the resource can be considered a strength or weakness. Therefore, the research method used is Mixed Method Research with the research aim of identifying Lantebung mangrove ecotourism resources, analyzing VR studies, and Lantebung mangrove ecotourism sustainability strategies. This research was conducted by placing resources and capabilities into five VRIOL categories. VRIOL is a tool for determining the nature of resources and capabilities. Meanwhile, the data collection technique is interviews and distributing questionnaires to 200 respondents using a sampling technique, namely purposive sampling. Furthermore, the data analysis technique used in this research is data triangulation. The research results show that VRIO analysis is used as a basis for identifying competencies possessed. To achieve a sustainable competitive advantage, these resources and capabilities must have four important attributes, namely valuable, rare, inimitable, and organized. This type of research is descriptive and qualitative research, data is collected using observation and interview methods. The research results show that there are sixteen types of resources in the Lantebung Mangrove Ecotourism consisting of tangible, intangible, and capability resources. Lantebung Mangrove Ecotourism has strategic strengths in sixteen resources at the Sustainable Competitive Advantage level.